1985
DOI: 10.1002/zaac.19855220321
|View full text |Cite
|
Sign up to set email alerts
|

Unvollständinge Chelatisierung durch N‐Acylthioharnstoffe: Die Struktur von Bis[N‐(1‐pyrrolidinyl‐thiocarbonyl)‐benzamidato]quecksilber(II)

Abstract: Bis[N‐(1‐pyrrolidinyl‐thiocarbonyl)‐benzamidato] quecksilber(II) kristallisiert onoklin in der Raumgruppe P21/c mit den Gitterkonstanten a = 10,126, b = 22,347, c = 11,384 Å, β = 109,13° und Z = 4. Gelöst wurde die Struktur durch Anwendung direkter Methoden auf Differenzstrukturfaktoren (DIRDIF). Für 2195 beobachtete Reflexe betrug der abschließende R‐Wert R = 0,06. Quecksilber besitzt die charakteristische Koordinationszahl 2 mit linearer Anordnung der beiden S‐Ligatoren. Die O‐Ligatoren zeigen jedoch noch sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

1985
1985
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 20 publications
1
13
0
1
Order By: Relevance
“…[278] The same group reported that (NBu 4 )[ReOCl 4 ] reacts with 1-benzoyl-3-picolyl thiourea (Hpicbtu) in acetone to form the deep-green oxorhenium(V) complex (NBu 4 ) 2 [{Re 2 O 2 Cl 5 (Hpicbtu)} 2 O] with the acylthiourea molecule showing an atypical bridging coordination geometry. [280] Monodentate neutral coordination (Scheme 17) solely through sulfur is less common, and a few examples were early reported with soft d 10 metal, such as Cu(I), [281,282] Ag(I), [283] Au(I), [241] and Hg(II) [284] complexes. This behavior resemble that encountered for the analogues 1-acyl-3-substituted selenoureas recently reviewed by Molter et al [285] and Molter and Mohr.…”
Section: Metal Complexesmentioning
confidence: 99%
“…[278] The same group reported that (NBu 4 )[ReOCl 4 ] reacts with 1-benzoyl-3-picolyl thiourea (Hpicbtu) in acetone to form the deep-green oxorhenium(V) complex (NBu 4 ) 2 [{Re 2 O 2 Cl 5 (Hpicbtu)} 2 O] with the acylthiourea molecule showing an atypical bridging coordination geometry. [280] Monodentate neutral coordination (Scheme 17) solely through sulfur is less common, and a few examples were early reported with soft d 10 metal, such as Cu(I), [281,282] Ag(I), [283] Au(I), [241] and Hg(II) [284] complexes. This behavior resemble that encountered for the analogues 1-acyl-3-substituted selenoureas recently reviewed by Molter et al [285] and Molter and Mohr.…”
Section: Metal Complexesmentioning
confidence: 99%
“…Despite the fact that aroylthioureas should possess a high affinity to thiophilic metal ions, surprisingly less is known about this area of their coordination chemistry. A survey of the literature reveals only a few reports of aroylthiourea complexes with thiophilic ions such as Ag + , Au + ,, Hg 2+ , or Cu + . Nevertheless, some of these complexes show very interesting structural characteristics, for example, a discrete 26‐membered bimetallamacrocycle of Hg 2+ ions with {L para } 2– ligands is formed, in which the linear coordination preference of mercury(II) ions for the sulfur donor atoms is established .…”
Section: Introductionmentioning
confidence: 99%
“…Sie reagieren mit Übergangsme tallionen zumeist monoanionisch und zweizähnig unter Deprotonierung und Bildung von Neutral komplexen mit S, O-Koordination [6][7][8][9][10], obwohl auch anderes Koordinationsverhalten beobachtet wurde [11][12][13].…”
Section: Introductionunclassified